ICMPv6-Based DoS and DDoS Attacks and Defense Mechanisms: Review. Issue 4 (4th July 2017) - Elejla, Omar E.; Anbar, Mohammed; Belaton, Bahari
ABSTRACT: The number of internet users and devices that are in need for more IP addresses to be assigned to them is rapidly increasing. A new protocol named IPv6 was developed in 1998 to overcome the addressing issue and to improve network communications in general. IPv6 is an improved protocol compared to IPv4 in terms of security since it provides built-in security mechanisms, such as IPSec. In addition, it brought new functionalities, such as Neighbour Discovery Protocol (NDP) procedure, which depends on Internet Control Message Protocol version 6 (ICMPv6) protocol messages. However, IPv6 inherited a number of attacks from IPv4 in addition to new attacks it brought within its new features. One of the most common attacks is the Denial of Service (DoS) attack due to its ease of being launched in different ways. A more serious DoS attack can be launched from many hosts called Distributed Denial of Service (DDoS). DoS and DDoS attacks are thorny and a grave problem of today's internet, resulting in economic damages for organizations and individuals. Therefore, this paper is created to study the properties of DoS and DDoS attacks against IPv6 networks using ICMPv6 messages. Additionally, it analyzes the various existing detection and prevention approaches that are proposed to tackle ICMPv6-based DoS and DDoS attacks. Moreover, it explains the existing tools that might be used for performing these attacks.